(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Entrepreneurship education in M.P has gainedrelevance in today’s context. Education in the area of entrepreneurship mayhelp people to develop skills and knowledge, which could benefit them forstarting, organizing and managing their own enterprises. It has been realizedthat the educational institutions do not offer any assurance to get access toemployment in the formal job market. Entrepreneurship education is extremelyimportant as it encourages innovation, fosters job creation, and improvesglobal competitiveness with the success of entrepreneurs.